Ghrelin reverses ductular reaction and hepatic fibrosis in a rodent model of cholestasis - Anca D. Petrescu (Nature Portfolio, 2020)
Abstract The orexigenic peptide ghrelin (Ghr) stimulates hunger signals in the hypothalamus via growth hormone secretagogue receptor (GHS-R1a). Gastric Ghr is synthetized as a preprohormone which is proteolytically cleaved, and acylated by a membrane-bound acyl transferase (MBOAT). Circulating Ghr is reduced in cholestatic injuries, however Ghr’s role in cholestasis is poorly understood. We investigated Ghr’s effects on biliary hyperplasia and hepatic fibrosis in Mdr2-knockout (Mdr2KO) mice, a recognized model of cholestasis. Serum, stomach and liver were collected from Mdr2KO and FVBN control mice treated with Ghr, des-octanoyl-ghrelin (DG) or vehicle. Mdr2KO mice had lower expression of Ghr and MBOAT in the stomach, and lower levels of circulating Ghr compared to WT-controls. Treatment of Mdr2KO mice with Ghr improved plasma transaminases, reduced biliary and fibrosis markers. In the liver, GHS-R1a mRNA was expressed predominantly in cholangiocytes. Ghr but not DG, decreased cell proliferation via AMPK activation in cholangiocytes in vitro. AMPK inhibitors prevented Ghr-induced FOXO1 nuclear translocation and negative regulation of cell proliferation. Ghr treatment reduced ductular reaction and hepatic fibrosis in Mdr2KO mice, regulating cholangiocyte proliferation via GHS-R1a, a G-protein coupled receptor which causes increased intracellular Ca2+ and activation of AMPK and FOXO1, maintaining a low rate of cholangiocyte proliferation.